Dietetic treatment of diabetes - Hall, Mary Elizabeth Longfellow (My University, 1904)
Introduction: In medical practice of recent years physicians are realizing more and more the truth of the statement that the health of the patient depends upon the food taken into the body. Let us consider for a moment what a food is. It is anything which when taken into the body is capable of repairing wasted tissue, or furnishing it with material from which to produce heat, nervous or muscular force. It is impossible to replace wasted tissue when nothing is given to the organism with which to replace the wornout body. Thus we see that feeding is one of the most important factors in the regaining of health to a sick person. In some cases it holds a more important place than drugs. The diet is very important in Uraemia, Aneamia, Albuminuria and Diabetes. Let us consider the last named. Diabetes is a disorder of nutrition in which sugar accumulates in and is excreted by the urine in the form of grape sugar or glucose. For a case to be considered diabetes mellitus, it is necessary that the form of sugar eliminated in the urine…
Citation: Hall, Mary Elizabeth Longfellow. Dietetic treatment of diabetes. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Diabetes; Disease; Disease Treatment; Dietetics; Theses; Manuscripts (documents)